Rosmarinic acid alleviates intestinal inflammatory damage and inhibits endoplasmic reticulum stress and smooth muscle contraction abnormalities in intestinal tissues by regulating gut microbiota - Kan Li; Jiawei Wu; Shuang Xu; Xueying Li; Yanhe Zhang; Xue-jiao Gao (Microbiology Spectrum, 2023)
ABSTRACT The host–bacterial interactions play the key role in inflammatory bowel disease (IBD). Dysbiosis of the intestinal flora can lead to pathological changes in the intestine. Rosmarinic acid (RA) is a natural phenolic acid compound with antioxidant, anti-cancer, anti-inflammatory, anti-apoptotic, anti-fibrotic, and anti-bacterial activities that has a palliative effect on acute IBD. We have established an in vivo model for mice. Histological staining was performed to directly observe RA alterations in the intestinal tract. The alteration of RA on mouse intestinal flora was observed by 16S rRNA high-throughput sequencing, and the effect of RA on intestinal mechanism of action was detected by qPCR and western blot. The results showed that RA had a significant protective effect on the intestine. RA upregulated the abundance of Lactobacillus johnsonii and Candidatus Arthromitus sp SFB-mouse-NL and downregulated the abundance of Bifidobacterium pseudolongum, Escherichia coli, and Romboutsia ilealis. RA downregulated the expressions of ROCK, RhoA, CaM, MLC, MLCK, ZEB1, ZO-1, ZO-2, occludin, E-cadherin, IL-1β, IL-6, TNF-α, GRP78, PERK, IRE1, ATF6, CHOP, Caspase12, Caspase9, Caspase3, Bax, Cytc, RIPK1, RIPK3, MLKL, and upregulated the expression of IL-10 and Bcl-2. These results displayed that RA inhibited the inflammation, which is caused by tight junction damage, by repairing intestinal flora dysbiosis, relieved endoplasmic reticulum stress, inhibited cell death, and corrected smooth muscle contractile dysregulation. The results of this study revealed RA could have a protective effect on the small intestine of mice by regulating intestinal flora. IMPORTANCE Inflammatory bowel disease (IBD) is a chronic, relapsing, remitting disorder of the gastrointestinal system. In this study, we investigated the protective effects of rosmarinic acid on the intestinal tract. The results showed that RA was effective in reducing inflammatory damage, endoplasmic reticulum stress, smooth muscle contraction abnormalities, and regulating intestinal flora disorders.